Stylized character designs and animation for ‘Charlie’ - Ong, Yi Teck (2019)
This document covers the character design and animation process for the film ‘Charlie’. It discusses the importance of achieving ‘caricatures’ instead of going for naturalistic depiction of characters. This report will discuss the delivery of Charlie Chaplin’s performance in terms of character archetypes, character design and movement and how these lessons are integrated into the film ‘Charlie’.